1999
DOI: 10.1088/0305-4470/32/38/301
|View full text |Cite
|
Sign up to set email alerts
|

On the possibility of decoherence due to a relativistic effect

Abstract: This note looks at the possibility of a system of free particles presenting decoherence in the total momentum when tracing upon their relative momenta if we take into account a relativistic correction to the expression of the kinetic energy.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2018
2018
2018
2018

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 33 publications
0
3
0
Order By: Relevance
“…In this paper, we focus on its intrinsic origin which results in the minimum decoherence even in the absence of any usual environments. It has been found that the collective mode of MOs can be coupled with its inner motion modes [17,18]. C. Carazza has studied the decoherence effect of the collective variable for free quasi-relativistic particles [18].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…In this paper, we focus on its intrinsic origin which results in the minimum decoherence even in the absence of any usual environments. It has been found that the collective mode of MOs can be coupled with its inner motion modes [17,18]. C. Carazza has studied the decoherence effect of the collective variable for free quasi-relativistic particles [18].…”
Section: Introductionmentioning
confidence: 99%
“…It has been found that the collective mode of MOs can be coupled with its inner motion modes. [17][18][19] Carazza has studied the decoherence effect of the collective variable for free quasi-relativistic particles. [19] Nevertheless, for macroscopic objects, a more reasonable scenario should take the interaction between particles into account, since it is the coupling between particles that bound them into a macroscopic object.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation